(untitled) (Italian Journal of Public Health, 2012)
Background: acanthamoeba keratitis (a.k.) is a rare secondary infection due to acanthamoeba (a) invading the cornea. cofactors of risk may include TrauMa and contact lenses (cL). The objectives of this observational study are to evaluate the occurrence of a.k. in patients accessing the department of Special Senses of the Teaching Hospital “Policlinico umberto I” of rome with ocular infections dur- ing the period from 2005 to 2011, and the role played by risk factors which included contact lenses, TrauMa, sex and age. MeTHodS: a case-control study involving 714 subjects was conducted (350 male and 364 female). all of the patients underwent a thorough ocular examination with confocal microscopy and a review of their medical history to outline relevant variables (contact lens and TrauMa). Statistical analysis calculated the frequency distribution and the odds ratio (or) (95%cI) for the risk factors “contact lenses” (cL) and “TrauMa”. The odds ratio (95%cI) was adjusted for age and sex trough Logistic regression. reSuLTS: out of 714 patients, 11 patients (7 male and 4 female) with a mean age of 34.09 years (19 to 51 years old) were found to be affected by a.k. The age group most afflicted ranged from 30 to 51 years old. Statistical analysis produced a crude or equal to 17.68 (95%cI 2.25-138.89) for cL-a.k. and or equal to 7.71 (95%cI 0.89-66.75) for ocular TrauMa.-a.k. Logistic regression performed to adjust or for age and sex showed the following values, respectively: or*=82.54 (95%cI 3.04-2239.58) and or*=11.52 (95%cI 1.19-111.76). concLuSIonS: The data highlights an increase in a.k. cases during the 6 year study period. The association between this pathology and the use of contact lenses and/or TrauMa has been statisti- cally proven. The strength of this association increases when the odds ratio (or*) is adjusted for the confounding risk factors of age and sex. When dealing with the topic of acanthamoeba keratitis, it is important to remember that educating patients on proper hygiene practice for contact lenses is the first step towards preventing a.k. The results obtained are important because they are derived from the first Italian case-control study on a.k.